On-line identification of magnetizing inrush and internal faults in three-phase transformers - SIDHU, T. S; SACHDEV, M. S (IEEE transactions on power delivery, 1992)
The authors present a microprocessor-based system for online identification of magnetizing inrush and internal fault conditions in three-phase transformers. The system uses a digital algorithm which is based on a transformer model and can be used irrespective of whether or not it is possible to measure winding currents. The only parameters needed by the algorithm are positive and negative sequence impedances of the transformer. These parameters are usually a part of the name-plate data. The proposed algorithm has been implemented on a Texas Instrument TMS320C25 digital signal processor. The hardware and software of the system are described. The ability of the system to identify magnetizing inrush and internal faults was tested by using a 15 kVA three-phase transformer. Some test results are reported.